Ação rescisória por violação de princípio - Coelho, Otávio Ribeiro (2022)
This monograph intends to present an analysis and interpretation regarding article 966, item V of the Brazilian Civil Procedure Code, which authorizes the filing of a motion (rescissory action) in cases of violation of a legal rule. The research focuses specifically on the possibility of the system file this special motion in cases that the res judicata has violated a legal principle. In order to do so, the dissertation brings an exposition of the function of legal principles in the Brazilian legal system, analyzing its historical conceptual evolution, from the system of natural law to the current post-positivist moment, contextualizing the normative function of principles in contemporary neoconstitutionalism. The research also demonstrates the necessary concern of effectiveness in the civil process, outlining the bases of a civil process of results, concerned with social transformation and the factual peculiarities of the case to be judicially resolved. The difference in legal nature between rules and principles is exposed, and how the different normative conflicts within the legal system are resolved. The monograph also exposes a conceptual analytical study about the institute of res judicata, approaching its evolution in Brazilian history and its main legal and political functions, demonstrating its constitutional matrix and its role in the civil process. Also, the monograph presents the institute of rescissory action in the civil procedure system, with a conceptual exposition of this action and its normative bases, focusing on the possibility of rescissory action for violation of the legal rule, expressly contained in the aforementioned legal provision of the Code of Civil Procedure . From this legal authorization, an interpretation is constructed in order to authorize the filing of the rescission action for violation of legal principle